Assessing HRM’s function “Recruitment & Selection Process” of Summit Communications Ltd. - Maysha, Sanjida Hossain (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.